Toxicity studies of natural product in vero cells using impedance monitoring - Hamdan, Taufik Hakim; Mansor, Ahmad Fairuzabadi; Abbas, Phirdaous; Nordin, Anis Nurashikin; Hashim, Yumi Zuhanis Has-Yun (2017)
Natural products have traditionally been used for medicinal purposes in Asian communities. Toxicity studies typically use animal testing to predict the harmfulness of a particular substance to human health. For this study, in lieu of animal testing, we utilize cell-based biosensors to evaluate the toxicity of natural products. The cell-based biosensors are fabricated on a printed circuit board with copper electrodes and are equipped with PDMS cell culture chambers. Two different electrodes (interdigitated and circular) were designed. Vero cells were used to represent normal healthy cells. The cells are first cultured on biosensors and then are inoculated with natural products, Taxol (chemo drug – positive control) and DMSO (negative control). Impedances of these biosensors were then recorded at six-hour intervals for 80 hours to determine the growth of the cells. It was found that compared to Taxol, natural products have a very low toxicant values.